PERBEDAAN PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI KELAS X SMA NEGERI 2 PEMATANGSIANTAR - Winmery Lasma Habeahan (Journal of Didactic Mathematics, 2020)
The purpose of this study was to determine the differences in the improvement of students' mathematical problem-solving abilities with the Contextual Teaching and Learning approach in the material of the two-variable linear equation system in class X SMA Negeri 2 Pematangsiantar. This study used an experimental method with the aim of being in accordance with the previous statement to determine the difference in students' mathematical problem-solving abilities with a contextual approach and an expository approach, with a randomized pretest-posttest control group design. The average increase in problem-solving abilities in the control class was 0.1688 while the increase in problem-solving abilities in the experimental class was 0.0085. By using the t-test (SPSS), with a value of Fcount = 10.907 and a significant level of 0.05, a significant probability is obtained 0.002 <0.05, it can be concluded that there is a difference in normalized gain or an increase in problem-solving ability with conventional and contextual approaches. Based on the average gain of the control and experimental classes, the increase in the control class using the conventional approach is higher than the experimental class with the contextual approach. The difference in increasing problem-solving abilities in conventional classrooms is possible due to differences in students' entry-level abilities, which can be seen in the average pretest of each class.